Effects of Artemisia argyi on Nonalcoholic Steatohepatitis and Changes in the Gut Microbiota - Erdenebileg, Saruul; Kim, Myung Suk; Nam, Yunseong; Nho, Chu Won (2022년도 한국식품영양과학회 국제심포지엄, 정기학술대회 및 정기총회 논문집, 2022)
Nonalcoholic steatohepatitis is one of the leading causes of fibrosis. Artemisia argyi (AA) has been a traditional medicine for alleviating pain in the lower abdomen, and inflammation. To determine the therapeutic effect of AA ethanol extract and its active compounds, we induced the fibrosis using TGF-β-treated human hepatic stellate LX-2 cells and a choline-deficient L-amino acid-defined high-fat diet (CDAHFD)-induced NASH model. Eupatilin, Chlorogenic acid, and Jaceosidin known to be isolated from AA ethanol extract significantly reduced the expression of fibrosis-related markers in LX-2 cells. In addition, oral administration of AA ethanol extract inhibited the production of liver injury markers, lipid profiling and mRNA expression of fibrosis-related markers. As a result of 16S rRNA sequencing analysis to determine whether the anti-fibrosis effect is mediated by intestinal microbes, the abundance of Acetivibrio ethanolgignens was significantly reduced by AA compared to the CDAHFD group and showed a significant correlation with fibrosis-related markers. These results suggest that AA is a promising therapeutic candidate for fibrosis and liver disease in CDAHFD-induced mice.